TEST THE CONTENT OF GLOBULIN, BIURET AND HEMOGLOBIN IN BLOOD IN ADOLESCENT WOMEN - Rita Amini Warastuti; Vira Yuniar J. Paute; Sri Masyita D. Jailani (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Blood is a liquid found in humans and all high-level animals that serves to transmit substances and oxygen needed by the body's tissues, transport chemicals from metabolism, and also as a defense of the body against viruses or bacteria. This study aims to find out the content of globulin and biuret in the blood of adolescent women and identify hemoglobin levels contained in this. Method used in this study is qualitative research that is descriptive, with sampling techniques that use purposive sampling method. The results showed that in this globulin test aims to see the presence of globulin or protein deposits in serum and the results obtained are deposits in serum samples. Then the biuret test aims to see the discoloration, and the result Occurs discoloration of the serum (white) and for this hemoglobin test aims to see if the sample blood is normal or not and the result is normal sample blood.